Coding activities for building websites with HTML - Furgang, Adam (Code creator (Rosen Publishing Group), 2022)
"Creating a website can be loads of fun. With the use of the computer language HTML, it is possible for anyone to learn the basics and get started on the road to creating a website. The step-by-step activities in this title will help readers explore tags, color hex codes, URLs, linking webpages, and the use of graphics and photos--all of which are needed to design and craft a website. Beginners will quickly see how easy and rewarding it can be to code with these activities, which also contribute to career readiness in computer science"--